'When I find myself in times of trouble …' : The conditional effect of international organisations on policy convergence. (6th December 2012) - Fink, Simon
Abstract Most quantitative analyses of policy convergence treat transnational communication in international organisations and domestic economic problems as additive factors. By contrast, this article argues that domestic economic problems motivate governments to search for successful policies, while international organisations offer channels for policy learning. Thus, both factors interact, magnifying each other's effects. The argument is corroborated by a quantitative analysis of the privatisation of telecommunications providers in the Western OECD world. A dyadic logit model shows that joint membership in international organisations increases the likelihood of policy convergence if governments face budget deficits. The argument of the article builds a bridge between theories of international organisations and domestic theories of policy making. Theories of the former gain an important scope condition specifying the conditions under which transnational communication works, while exploring the latter gains a theory specifying where new policy ideas come from.